Happiness and religion in two Perus - Ibañez, Franklin (2020)
This article examines the relationship between happiness and religiosity in two groups of districts in Peru. Although it is known that there is a positive relationship between happiness and religion, there has not previously been interest in studying this relationship at either end of the social pyramid. The subjects of this research are not only the rich and the poor but those who live in the poorest and richest districts. This article has two sections. The first explains how religion is practiced at both ends of the social scale. The second shows the relationship between happiness and religion. The paper states that rich people are happier than the poor even if the disadvantaged group is more religious.